History Flows Through Us: Psychoanalysis and Historical Understanding. Issue 3 (3rd July 2017) - Frie, Roger
Abstract : This essay explores the notion that we are all fundamentally shaped by history. I suggest that psychoanalysis needs to attend not just to the history of the patient, but also to the fact that the psychoanalyst and patient alike are affected by history and its traumas. Human experience cannot be separated from the historical and cultural contexts in which we live out our lives. The approach I am describing is not an endorsement of historical determinism, the notion that the past entirely makes us who we are today. It is, rather, a plea to know history so that we might respond to what it can teach us. In making this argument, I draw on the work of the historian and psychoanalyst by training, Thomas Kohut. His work helps us to avoid reductionist views of human experience, whether in the past or the present, and teaches us to use empathy to think and feel our way into the situation of the other person. This is particularly relevant in light of the ongoing prejudices and social injustices in contemporary society.